Cell Phone Use While Driving: Prospective Association with Emerging Adult Use. (September 2017) - Trivedi, Neha; Haynie, Denise; Bible, Joe; Liu, Danping; Simons-Morton, Bruce
Highlights: Young driver secondary task engagement can be influenced by peer-reported engagement. Participants with peers who texted while driving were more likely to text and drive. Peer texting behavior influences the prevalence of texting among emerging adults. Abstract: Secondary task engagement such as cell phone use while driving is a common behavior among adolescents and emerging adults. Texting and other distracting cell phone use in this population contributes to the high rate of fatal car crashes. Peer engagement in similar risky driving behaviors, such as texting, could socially influence driver phone use behavior. The present study investigates the prospective association between peer and emerging adult texting while driving the first year after high school. Surveys were conducted with a national sample of emerging adults and their nominated peers. Binomial logistic regression analyses, adjusting for gender, race/ethnicity, parental education, and family affluence, showed that participants ( n  = 212) with peers ( n  = 675) who reported frequently texting while driving, were significantly more likely to text while driving the following year (odds ratio, 3.01; 95% CI, 1.19–7.59; P  = 0.05). The findings are consistent with the idea that peer texting behavior influences the prevalence of texting while driving among emerging adults.